SOCIAL CAPITAL AND THE MARTIAL LA W TECHNOCRACY: THE MAKING AND UNMAKING OF A POWER ELITE. - Encarnacion Tadem, Teresa S. (Kritika Kultura, 2013)
This paper attempts to show the extent to which a faction of the Philippine technocracy during the martial law years utilized its social capital (used interchangeably with cultural capital) to become a potent economic bloc in society only to see it gradually depleted.Led by then Prime Minister and concurrent Finance Minister Cesar E.A. Virata, this bloc consisted of key senior economic officials who were closely associated with IMF-World Bank policies. Their social capital was founded on their family and educational backgrounds, paving the way for their acquisition of the technical expertise required by the business community and later, by government. What set them apart from the other pre-martial law technocrats was their support for an export-oriented and foreign investment-friendly industrialization policy shared by Marcos and the IMF-World Bank. The social capital of this bloc grew due to their ability to access foreign loans, gain international support, and function as a deterrent to corruption.Marcos, however, proceeded to undermine this bloc's capital by doing the following: 1) limiting the Virata faction to the economic sphere and making sure it was not "politically-threatening"; 2) "factionalizing" the technocracy resulting in non-Virata technocrats pursuing their own projects; and 3) and nurturing crony capitalism and corruption through Mrs. Marcos and his "chief cronies" to the detriment of the Virata faction's economic policies.But despite the opportunity provided by the political and economic crisis of the early 1980s and initial IMF-WB support,the Virata-led bloc's social capital rapidly deteriorated because of its inability to now access the needed loans and the withdrawal of US support for the Marcos dictatorship. This further highlighted the unsustainable and relative vulnerability of its social capital.